The Influence of Sheikh Abdul Fattah in the Development of Islam in Natal City (1745-1855) - Siregar, Tamara Ivani; Achiriah, Achiriah (Yupa: Historical Studies Journal, 2024)
This article explores the pivotal role played by Sheikh Abdul Fattah in shaping the development of Islam in Natal City and its environs from 1745 to 1855. Initially, the populace of the South Tapanuli region was lacking in Islamic knowledge. However, with the advent of Sheikh Abdul Fattah, concerted efforts were made to enhance Islamic religious education. Through the establishment and nurturing of the Sheikh Abdul Fattah Private Islamic College (STAIS), he catalyzed profound transformations. STAIS was founded upon his return from studies in Makkah, where he effectively disseminated the knowledge acquired to his community in Natal. By implementing innovative approaches, STAIS Sheikh Abdul Fattah emerged as a beacon, attracting hundreds of students from Natal City and its vicinity, thus revolutionizing Islamic education in the area. The endeavor to cultivate a refined and progressive society became central to Sheikh Abdul Fattah's vision. Inspired by this ethos, he successfully revolutionized the landscape of Islamic education in Kota Natal, leaving an indelible mark on the expansion of religious knowledge and the advancement of Muslim civilization in the region.